2017
DOI: 10.1027/1614-2241/a000128
|View full text |Cite
|
Sign up to set email alerts
|

Building Latent Class Trees, With an Application to a Study of Social Capital

Abstract: Abstract. Researchers use latent class (LC) analysis to derive meaningful clusters from sets of categorical variables. However, especially when the number of classes required to obtain a good fit is large, interpretation of the latent classes may not be straightforward. To overcome this problem, we propose an alternative way of performing LC analysis, Latent Class Tree (LCT) modeling. For this purpose, a recursive partitioning procedure similar to divisive hierarchical cluster analysis is used: classes are spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Such a result can become exceedingly complicated and difficult to interpret, reducing the practical use of the model. To overcome this problem, Van Den Bergh et al (2017) suggested an extension to LCA, which they called Latent Class Trees (LCT) analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a result can become exceedingly complicated and difficult to interpret, reducing the practical use of the model. To overcome this problem, Van Den Bergh et al (2017) suggested an extension to LCA, which they called Latent Class Trees (LCT) analysis.…”
Section: Methodsmentioning
confidence: 99%
“…LCT analysis was developed to provide a solution to some common difficulties when interpreting LCA results, such as the absence of a distinct optimum number of classes that fits a model or the fact that it is often unclear how different model results are interconnected. LCT addresses these problems by imposing a hierarchical structure on the latent classes ( Van Den Bergh et al 2017 ). In short, LCT is defined by a structure of mutually linked classes that are formed by sequentially splitting classes into two subclasses (using LCA with weighted membership probabilities).…”
Section: Methodsmentioning
confidence: 99%
“…The bias-adjusted three-step method has become quite popular among applied researchers, but the basis of this method, the LC and LCG models, are not easy at all for applied researchers (Van De Schoot, Sijbrandij, Winter, Depaoli,& Vermunt, 2016). The tree approach facilitates the use of these models, which can lead to more interpretable and more meaningful classes.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the above-mentioned problems associated with LC analysis applications with large data sets, van den Bergh, Schmittmann, and Vermunt (2017) proposed an alternative way of performing an LC analysis, which they called latent class tree (LCT) analysis. Their approach involves performing a divisive hierarchical cluster analysis using an algorithm developed by Van der Palm, Van der Ark, and Vermunt (2016) for density estimation with a large number of categorical variables.…”
Section: Introductionmentioning
confidence: 99%